A STUDY ON SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 5 PEKANBARU - Kaffati, Nurul Hikma; Gultom, Effendy; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This is a descriptive qualitative research which is aimed at finding out the speaking ability of the second year students of SMAN 5 Pekanbaru. The sample of this research is obtained by using cluster random sampling. The intrument of the test is in the form of monologue. The students’ speaking scores are measured by three raters. After being measured, the data are analyzed by the writer. The result findings show that the mean score of the second year students’ speaking ability of is 53,7 which is categorized into mediocre level. The highest score is in terms of grammar and the lowest score is in terms of fluency.Key Words : Speaking, Ability, Speaking Ability